2021
DOI: 10.1021/acsanm.1c00987
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Size Effects in Biomedical Applications

Abstract: Nanoparticle size plays a central role in determining material properties and performance in biomedical applications. A wide variety of functional nanomaterials and nano-bioconjugates have been developed for monitoring biochemical activity, controlling biological functions, and therapeutic applications. This review focuses on the role of nanoparticle size (typically in the range of 1−100 nm) in various biomedical applications, the origin of such a size effect, and the optimum size requirement for the best perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 180 publications
(557 reference statements)
0
84
0
Order By: Relevance
“…CHA forms particles with diameters of approximately 8 ​nm, and CHA@GOx forms particles with sizes of approximately 20 ​nm. These sizes are conducive to the presentation of simulated enzyme activity [ 50 , 51 ]. Additionally, UV–vis examination demonstrated that free GOx and CHA@GOx that had been disintegrated under acidic conditions had the same UV–vis absorption peak at 280 ​nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CHA forms particles with diameters of approximately 8 ​nm, and CHA@GOx forms particles with sizes of approximately 20 ​nm. These sizes are conducive to the presentation of simulated enzyme activity [ 50 , 51 ]. Additionally, UV–vis examination demonstrated that free GOx and CHA@GOx that had been disintegrated under acidic conditions had the same UV–vis absorption peak at 280 ​nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the interaction between a nanomedicine and the outer membrane of cells is largely dependent on the material, size and shape of the nanostructure [8]. The influence of NP material and size is well documented and understood (see recent reviews [9][10][11][12]). The influence of nanomaterial shape is less documented in comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative is to produce small-size nanogels based on the clickable dextrans by an effective method such as the microfluidic technology for the promoted bioavailability of the nanogels in tumor. Recently, small-size nanoparticles as tumor-penetration delivery systems were documented, which displayed high permeability in deep tumor tissue enabling robust antitumor efficacy. In the future work, the CDP nanogels may be further developed for combination chemotherapy against cancers. …”
Section: Discussionmentioning
confidence: 99%